Outcome of Early Disposal of Lower Uterine Caesarean Section Patient from Hospital - A Randomized Clinical Trial (Ibrahim Cardiac Medical Journal, 2015)
Background and Objectives: Uncomplicated caesarean section patients are usually discharged from the hospital on the 7th postoperative day. Prolonged hospital stay increases the chance of nosocomial infections and facilitates them to spread rapidly. Experience shows that early discharge of patients reduces the chance of maternal and neonatal morbidities. The present study was done to assess the outcome patients discharged early from the hospital following caesarean section.Patients & Methods: The present randomized clinical trial was conducted in Dhaka Medical College Hospital, Dhaka Bangladesh from July 2006 - December 2006. A total of 300 term pregnant women admitted consecutively in the Obstetrics & Gynaecology Department of the Hospital and underwent elective or emergency caesarean section were included in the study. The patients were randomly divided into two study groups - early discharge group and usual discharge group. Patients of Group-A were discharged 72 hours after caesarean section and were advised to visit after 7th postoperative day for follow up, while the patients of Group-B stayed in the hospital for 7 days (including the day of operation) and outcome was evaluated on 7th postoperative day at discharge. The maternal outcome measures were urinary and respiratory tract infections (UTI and RTI), wound infection and puerperal sepsis and neonatal outcome variables were umbilical cord sepsis, septicemia and respiratory distress syndrome.Results: Of the 4,494 labour patients admitted during the 6 months study period, 1744(38%) needed caesarean section. Of them, 300 consecutive cases fulfilling the enrolment criteria were included in the study. The demographic variables studied were age, parity, socioeconomic condition. Types of caesarean section (elective or emergency) were also recorded. In 'Early discharge group' (discharge on 3rd postoperative day) out of 150 patients, only 50 patients returned for follow up on 7th postoperative day. Majority (84%) of them was free from any sorts of complications and very few of their neonates have had any complications. In 'Usual discharge group'(discharge on 7th postoperative day) out of 150 patients, 69(46%) cases developed complications. Of them wound infection was the leading complication (36%) followed by UTI (16%), RTI (9.3%), puerperal sepsis (8.0%), wound dehiscence (6.7%). Umbilical cord sepsis of newborn was also significant (17.3 %) in them. Other complications were considered negligible. Occurrence of overall complication was staggeringly lower in the former group than that in the later group (8% vs. 46%, p < 0.001).Conclusions: Early discharge of patients of caesarean delivery from hospital is safe for both mothers and neonates. It reduces unnecessary hospital burden and saves hospital resources.Ibrahim Cardiac Med J 2014; 4(1): 22-26